Analysis of the Effect of Liquidity, Profitability, and Debt to Equity Ratio (DER) on Firm Value in Mining Companies Listed on the Indonesia Stock Exchange - Masno Marjohan; Hadi Supratikta; Hilya Hasanah (Applied Information System and Management (AISM), 2023)
Firm value is the view of investors when measuring the success rate of a company. ROE is the variable most strongly associated with firm value to calculate the profit level of a company. Liquidity is a ratio to measure the company's ability to meet its short-term obligations. DER is a ratio used to assess debt against equity. The purpose of this study is to analyze the effect of liquidity (CR) on company value, profitability (ROE), and debt-to-equity ratio (DER) on company value and simultaneously in mining companies in the metal and mineral sub-sector listed on the Indonesia Stock Exchange for the period 2012–2021. This type of research is quantitative. The population in this study are mining companies listed on the Indonesia Stock Exchange. Samples were taken from 4 companies that met the criteria, with 10 years of observation totaling 40 sample units. The sampling technique used is the purposive sampling method. Data is downloaded via the website www.idx.co.id and the company's website. Data analysis uses descriptive analysis, the classical assumption test, regression analysis, hypothesis testing, and the determination coefficient test. The results of the study based on statistical calculations obtained simultaneous results that financial performance has no effect on the value of the company, while partial liquidity (CR) debt on equity (DER) has no effect on the value of the company, and profitability (ROE) significantly affects the value of the company.